The Moderating Impact of Entrepreneurial Orientation between Market Orientation and Performance of SMEs in the Post-Conflict Northern Province of Sri Lanka - S. Vaikunthavasan (Colombo Business Journal)
This study explores how market orientation influences SME performance, with entrepreneurial orientation as a moderating factor. This relationship remains underexplored in the context of SMEs in post-conflict emerging economic regions. Furthermore, conflicting findings in the current literature highlight the need for further investigation. This study applied a quantitative research methodology. A survey was conducted to collect data from respondents. The result revealed a significant positive impact of market orientation on performance, and entrepreneurial orientation strengthens the relationship between market orientation and performance. This framework highlights the importance of SMEs adopting a market-oriented approach while fostering an entrepreneurial culture. This study adds value by empirically validating a conceptual framework that emphasises the synergistic role of market and entrepreneurial orientations in enhancing SME performance in post-conflict emerging economies.